Misdiagnosed Frontal_Transethmoidal Meningoencephalocele : Case Report - Al-Fattani, Enas Hamed; Al-Jammal, Tariq Abdulfattah; Al-Aidarous, Tariq Ahmad (Journal of medical and pharmaceutical sciences, 2017)
To enhance awareness of healthcare providers for any baby comes with persistence unilateral nasal obstruction, and take care for him. Methods: A report of rare case for a child presented with an internal nasal mass with maternal history of folic acid deficiency Results: The diagnosis of transethmoidal encephalocele was confirmed by a computed tomography (CT) and magnetic resonance imaging(MRI). Craniotomy excision and duroplasty, assisted with endonasal endoscopic excision and repair of skull base defect by middle turbinate graft were done. Nasal tissue was taken for Histological examination which confirmed the diagnosis of an encephalocele within the nasal cavity. The patient had recovered with complete healing of grafts with no recurrence and follow up CT after 6 months was normal. Conclusion: The general physicians and pediatricians must put in consideration any baby with unilateral persistence nasal obstruction which can be frontal-transethmoidal meningocele +/- encephalocele . Taking folic acid or food rich of folate during pregnancy can help in reduction of neural tube defects prevalence. Radiological imaging (CT +/- MRI) study should be done for every Pediatric case presenting with an intranasal mass before any surgical intervention or an invasive intranasal procedure.